1968
DOI: 10.1042/bj1090209
|View full text |Cite
|
Sign up to set email alerts
|

A new route to the imidazole-2-thiones from 2-thiohydantoins. Implications in the study of ergothioneine

Abstract: 1. 2-Thiohydantoins are reduced by borohydrides to 4(5)-hydroxyimidazolidine-2-thiones, which eliminate water in acid to form imidazole-2-thiones. Both steps take place in mild conditions, in high yield. A number of imidazole-2-thiones have been synthesized by this sequence of steps, with one, two or three substituents in the 1-, 3- and 4(5)-positions. 2. 4(5)-Hydroxyimidazolidine-2-thiones are ammonium pseudo-bases, giving rise to an equilibrium mixture of amino aldehyde, carbinolamine and mesomeric ammonium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

1970
1970
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…The classical preparation of 2-thiohydantoins (2THs) is identical in concept to that of I2Ts; acylation of an a-amino ester or acid with a thiocyanate is followed by cyclization of the intermediate. [22][23][24][25][26][27][28] This reaction also traces back at least as far as Marckwald and co-workers. More recently it became famous as the basis of the Edman degradation, wherein the unmasked N-terminus of a peptide is acylated with a thiocyanate; cyclization at the resultant athioureido amide terminus expels a 2TH and a peptide shortened by one amino acid residue.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…The classical preparation of 2-thiohydantoins (2THs) is identical in concept to that of I2Ts; acylation of an a-amino ester or acid with a thiocyanate is followed by cyclization of the intermediate. [22][23][24][25][26][27][28] This reaction also traces back at least as far as Marckwald and co-workers. More recently it became famous as the basis of the Edman degradation, wherein the unmasked N-terminus of a peptide is acylated with a thiocyanate; cyclization at the resultant athioureido amide terminus expels a 2TH and a peptide shortened by one amino acid residue.…”
supporting
confidence: 68%
“…3,4,[16][17][18] This entry to an I2T and oxidative desulfurization of it (with nitric acid) dates back at least to Marckwald's 1892 report. 19 Alternative I2T syntheses include condensation of thioureas with a-hydroxycarbonyls, 20 and metal hydride reduction of an a-thioureido ester 21 or a 2-thiohydantoin (2TH) 22 followed by dehydration of the intermediate.…”
mentioning
confidence: 99%
“…1‐Butyl‐3‐methylimidazole‐2‐thione ( 5 ) was isolated in good yield after chromatography. This plan was changed upon finding that 3 completely cyclized to 4 thermally, that 4 was sufficiently electrophilic to undergo sodium borohydride reduction,61 and that crude 4 could be used. We later found the cyclization proceeded more easily with ethanolic potassium hydroxide, and accomplished a water‐insensitive one‐pot synthesis of 5 from 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The sequence furnishes ILs with varied imidazolium ring substitutents, as seen in the synthesis of [dpim] salts. The sodium borohydride reductions of hydantoins61 with or without their isolation and the one‐pot preparation of 7 are striking, as is the two‐step synthesis of [C 1 mim][OBz] from commercially available sarcosine methyl ester hydrochloride. This protocol also provides a hitherto unknown route to [C n tz] ILs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Scott and Henderson (15) suggested that ergothioneine is an artifact of isolation derived from an imidazolidine-2-thione present in the original biological material and formed during isolation (acid conditions). It seems unlikely that this is the case in any of our work because of the very mild conditions of extraction employed.…”
Section: Resultsmentioning
confidence: 99%